APPLICATION OF NATURAL LAW THEORY (THE NATURAL RIGHT) TO PROTECT THE INTELLECTUAL PROPERTY - Prasetyo Hadi Purwandoko; M. Najib Imanullah (Faculty of Law, Universitas Sebelas Maret, 2017)
The theory of natural law is usually used as a moral and philosophical foundation in order to protect the individuals property rights of Intellectual Property (IP). Philosophically, the protection of Intellectual Property Rights (IPR) can not be separated from the dominant thought that emphasizes the doctrine of natural human factors research. This study is legal research by using law and historical approach. The analysis of primary data is qualitatively through internal valuing to obtain a complete understanding (verstehen), while the secondary data such as law material is analyzed using hermeneutics (interpretation), content analysis and deductive method. The result shows that in respect of the development of the theory of natural law, there are four dominant theory of natural law to examine IP namely utilitarian theory, labor theory, personality theory, and social-planning theories. Moral doctrine which is based on natural law was adopted by the IPR regime to protect the individual owners of IPRs in order to that rights would not be violated by others. The natural law theory (the natural right) is still relevant to be used as a moral and philosophical foundation for the protection of IPR, as an individual property rights.